Akuntabilitas Pelaporan Dana Desa (Studi Kasus di Desa Gondosari, Kecamatan Punung, Kabupaten Pacitan Tahun 2016) - Wulandari, Fita Rahma, Drs. Achmad Muthali'in, M.Si (2016)
This study aimed to describe the village fund management accountability reporting in the Village District of Punung Pacitan Gondosari include implementation, obstacles encountered, and the solutions provided. This study used a qualitative research with case study strategy. Data collected by observation, interview and documentation. Test the validity of the data by triangulation of data sources and data collection techniques. Analysis of the data using interactive analysis techniques through data collection, data reduction, presentation and conclusion. The results of this study indicate that the village fund management accountability reporting in the Village District of Punung Pacitan Gondosari already performing quite well but there are still constraints faced. These constraints include lack of discipline TPK (Project Management Team) in reporting so that sometimes an accountability report that should have been reported yet to be reported in a timely manner, the lack of openness to the villagers, the villagers are less active role on the implementation of meetings or coordination related to the management the village fund. The solution that has been done is to give sanction strikes and cuts salaries to officers who have a duty or responsibility to make the accountability report of activities in the village, then the government must be more open with the public by way of involving the community when there are meetings or coordination regarding fund village in the village of the District Gondosari Punung Pacitan.